The effect of common market on european banking system and what will be the effect on Turkish banking system if Turkey accepted to EC - Karataş, Betül (My University)
unknown
Keywords: Avrupa Birliği; Bankalar ve Bankacılık; Bankalar ve Bankacılık_Avrupa Birliği